Citrus Diseases Exotic to Florida: Mal Secco - Kuang-Ren Chung (EDIS, 2012)
Mal secco, Italian for "dry disease", is a fungal disease that causes serious damage to a number of citrus cultivars in the Mediterranean and Black Sea areas but has not been reported in other citrus-growing regions. The main diagnostic field symptom is that wood of affected limbs has a reddish-yellow stain. This 3-page fact sheet was written by K.-R. Chung, and published by the UF Department of Plant Pathology, February 2012.